Beta-Elemene Reduces the Malignancy of Non-Small Cell Lung Cancer by Enhancing C3orf21 Expression - Cai, Hu; Ren, Lili; Wang, Ying; Zhang, Yongjun (Frontiers in Oncology, 2021)
Background: Elemene has potent anti-tumor effect, but its anti-tumor mechanism remains unclear. Chromosome 3 open reading frame 21 (C3orf21) acts as a tumor suppressor. This study tested whether the anti-tumor effect of Elemene was associated with modulating C3orf21 expression in non-small cell lung cancer (NSCLC). Materials and Methods: The impact of Elemene on C3orf21 expression in NSCLC cells was quantified. The stable C3orf21 silencing and over-expressing A549 and PC-9 cells were established and their effects on the Elemene-attenuated proliferation, wound healing and invasion of NSCLC cells as well as the expression of key regulators and signal events were determined.Results: Elemene significantly up-regulated C3orf21 expression in NSCLC cells. Elemene treatment significantly attenuated the proliferation, wound healing and invasion of NSCLC cells, which were significantly mitigated by C3orf21 silencing, but enhanced by C3orf21 over-expression. Similar patterns of Elemene-modulated cyclinD1, c-Myc, COX2, MMP2, MMP9, VEGF, PTEN and Notch1 expression were detected in NSCLC cells. Conclusions: Such data indicated that Elemene treatment attenuated the malignancy of NSCLC cells by up-regulating C3orf21 expression. Our findings may provide new mechanisms underlying the pharmacological action of Elemene.